Retrofitting micro gas turbines for wet operation. A way to increase operational flexibility in distributed CHP plants. (15th September 2015) - Stathopoulos, P.; Paschereit, C.O.
Highlights: Thermodynamic modeling of wet micro gas turbines. Technoeconomic analysis of mGTs retrofits for wet operation. Demonstration of the operational flexibility increase due to wet operation. In depth case study analysis of a CHP system in 15-min time-intervals. Sensitivity analysis on all major economic parameters of wet operation. Abstract: It is generally accepted that only flexible CHP plants could be a viable option in an electrical system with high penetration of variable renewables. Variable power-to-heat-ratios and decoupled power and heat generation will be basic requirements. Currently, the most common way to fulfill these specifications is the use of heat storage devices, whereas wet operation of gas turbines is an alternative way to achieve both goals. The current work is an analysis of a micro gas turbine adapted to operate with steam injection. A thermodynamic model is developed and a typical apartments building in Berlin, Germany is chosen as a case study. The study presumes the existence of a micro gas turbine and analyzes the results of its adaptation for wet operation. The environmental and economic performance of the new system is compared to that of its commercial counterpart. It is shown that the retrofitted turbine has longer annual operation time and higher electrical energy generation. The retrofit also proves to be an attractive investment for the German CHP market with internal rates of return reaching almost 20%.